2010
DOI: 10.1111/j.1744-7429.2010.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Maya Agroforestry Echoing Through Spatial Relationships in the Extant Forest of NW Belize

Abstract: Previous research has shown that ancient Maya 'forest gardens'-tree-dominated home gardens containing a diversity of tree species used for daily household needsstill resonate in the species composition of the modern forest. Centuries of positive interspecies interactions may enhance the reproductive and survival success of garden species selected and encouraged by experienced Maya forest gardeners. We hypothesized that such interaction may result in aggregated spatial patterns between 32 pre-selected, commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…In fact, the population density of adult trees of both species in the areas used for extraction of NTFPs was found to be between three and six times higher than in the undisturbed forest. This has been found for other species producing NTFPs in natural forests of the Amazon and in other tropical areas (Posey, 1985;Pinedo-Vasquez and Padoch, 1996;Miller and Nair, 2006;Bhagwat et al, 2008;Guix, 2009;Ross and Rangel, 2011). For instance, the 'castanhais' are aggregations of Brazilnut trees (Bertholletia excelsa Humb.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, the population density of adult trees of both species in the areas used for extraction of NTFPs was found to be between three and six times higher than in the undisturbed forest. This has been found for other species producing NTFPs in natural forests of the Amazon and in other tropical areas (Posey, 1985;Pinedo-Vasquez and Padoch, 1996;Miller and Nair, 2006;Bhagwat et al, 2008;Guix, 2009;Ross and Rangel, 2011). For instance, the 'castanhais' are aggregations of Brazilnut trees (Bertholletia excelsa Humb.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, the moist microenvironments of sinkholes in northern Yucat an harbor cacao, which indigenous Maya farmers continue to maintain and may have done so for many years (G omez-Pompa et al, 1990). The "feral garden" concept comes from Ross (2011) and Ross and Rangel (2011), who found greater diversity of useful tree species to be correlated with denser Maya sites, which they attributed to long-term impacts of ancient Maya forest use. Also, Hightower et al (2014) used Lidar to study forest canopies at Caracol and found terraced slopes gave rise to significantly different forests, which had more vertical diversity, greater height, and fewer gaps, as we would expect where soils are thicker, younger, and can store more water and nutrients.…”
Section: Synthesis: Impacts On Vegetationmentioning
confidence: 99%
“…Nonetheless, there have been many ecological studies of human impacts on Amazonian forests (Roosevelt, 2013), but as in the Maya region, we have only a preliminary assessment of these anthropogenic forests. Paleoecological and botanical studies have attempted to get at the long-term impacts of the Maya on regional forests, and a few botanical studies have focused on what the current forest can tell us about the past G omez-Pompa et al, 1987;McSweeney, 1995;Schulze and Whitacre, 1999;White and Hood, 2004;Hayashida, 2005;Campbell et al, 2006;Ross et al, 2011;Hightower et al, 2014;Lentz et al, 2015;Thompson et al, 2015). The legacy of "Mayacene" forest impacts may take many forms, such as greater dominance of useful species due to ancient plantation remnants or non-useful species because of ancient over-harvesting.…”
Section: Synthesis: Impacts On Vegetationmentioning
confidence: 99%
“…Many areas of tropical forest have a long history of anthropogenic disturbance, including clear felling and fire, that still influences the composition of forests we today regard as ‘pristine’ (Brncic et al. , 2007; Ross & Rangel, 2011). In many tropical countries a substantial proportion of the population is dependent upon shifting agriculture, where fire is an integral part of a ‘forest–fallow’ cycle alternating between crop land and secondary forest regrowth over decades.…”
Section: Fire In Tropical Forests: Simplistic Models and Complex Probmentioning
confidence: 99%